Implementing innovative social investment : strategic lessons from Europe / edited by Susan Baines [and three others]. - Baines, Susan (Policy Press, 2019)
Brings the regional and local to the forefront of social investment debates by showcasing original, evaluative evidence from ten European countries, and provides practical, accessible illustrations of good practice, routes to success, and lessons learned.